Threonine 80 phosphorylation of non‐structural protein 1 regulates the replication of influenza A virus by reducing the binding affinity with RIG‐I. (4th August 2016) - Zheng, Weinan; Cao, Shuaishuai; Chen, Can; Li, Jing; Zhang, Shuang; Jiang, Jingwen; Niu, Yange; Fan, Wenhui; Li, Yun; Bi, Yuhai; Gao, George F.; Sun, Lei; et al.
Summary: Influenza A virus evades host antiviral defense through hijacking innate immunity by its non‐structural protein 1 (NS1). By using mass spectrometry, threonine 80 (T80) was identified as a novel phosphorylated residue in the NS1 of the influenza virus A/WSN/1933(H1N1). By generating recombinant influenza viruses encoding NS1 T80 mutants, the roles of this phosphorylation site were characterized during viral replication. The T80E (phosphomimetic) mutant attenuated virus replication, whereas the T80A (non‐phosphorylatable) mutant did not. Similar phenotypes were observed for these mutants in a mouse model experiment. In further study, the T80E mutant decreased the binding capacity between NS1 and viral nucleoprotein (NP), leading to impaired viral ribonucleoprotein (vRNP)‐mediated viral transcription. The T80E mutant was also unable to inhibit interferon (IFN) production by reducing the binding affinity between NS1 and retinoic acid‐induced gene 1 protein (RIG‐I), causing attenuation of virus replication. Taken together, the present study reveals that T80 phosphorylation of NS1 reduced influenza virus replication through controlling RIG‐I‐mediated IFN production and vRNP activity.